Tertiary coal-bearing heterolithic packages as low permeability reservoir rocks in the Balingian Sub-basin, Sarawak, Malaysia - Nugraheni, R.D. (Geological Society of Malaysia, 2014)
Between 1930 and 1940, oil shows as well as gas that existed in the reservoir in gaseous phase rather than in solution (free gas) were found in the Mukah area. However, none of the discoveries were developed. Drilling results suggest that oil shows are common, while gas shows are present at deeper depths. Exploration requires a knowledge of heterogeneities in the rock. This paper is an introduction to a thematic set on the characterization of strata which acts as a reservoir for hydrocarbon gas and focuses on two main topics: (1) heterolithic facies and (2) diagenesis.The Balingian Sub-basin contains more than 6 km of sediment infill and is believed to be an important hydrocarbon kitchen. The coal-bearing sedimentary packages are composed of shale or mudstone, alternating with sandstone layers of varying lateral extent and locally intercalated with coal beds. These were deposited in Upper Miocene tide-influenced or tide-dominated deltaic and estuarine environments. However, some coals and carbon derived from the hydrogen-rich parts of plants such as cuticles and spores or sporinite might have generate and expel oil. Diagenetic events were an additional aspect that affects the reservoir quality. Clay cements have grown as a combination of grain-coating or pore-lining and pore throat blocking clots. The pore throat blocking cements caused a rapid decrease of porosity, so that it had an effect on the permeability similar to that of ductile grain compaction. The grain-coating and pore-lining cements in contrast caused a slight reduction in the permeability as the pore-throats were only partially blocked. A better understanding of the coal- bearing heterolithic strata through assessment may lead to the discovery of new unconventional hydrocarbon reserves. Â© 2014, Geological Society of Malaysia . All rights reserved.